Pengaruh Kualitas Pelayanan dan Lingkungan Kampus terhadap Motivasi Belajar Mahasiswa S1 Akuntansi Universitas Pamulang - Sadewa, Prima; Prasetya, Eka Rima (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
The aims of this research are (1) to determine the effect of service quality on student learning motivation, (2) to determine the effect of the campus environment on student learning motivation, and (3) to determine the effect of service quality and the campus environment simultaneously on student learning motivation. This research is research that uses a quantitative approach. Furthermore, this research is a type of associative research. The data collection technique is in the form of a questionnaire. The data analysis methods in this research are data quality testing, classical assumption testing, regression testing and hypothesis testing. The results of this research are as follows: (1) there is an influence of service quality on student learning motivation, (2) there is an influence of the campus environment on student learning motivation, (3) there is a simultaneous influence of service quality and campus environment on student learning motivation.